A novel re-attachable stereotactic frame for MRI-guided neuronavigation and its validation in a large animal and human cadaver model. (11th September 2018) - Edwards, Christine A; Rusheen, Aaron E; Oh, Yoonbae; Paek, Seungleal B; Jacobs, Joshua; Lee, Kristen H; Dennis, Kendall D; Bennet, Kevin E; Kouzani, Abbas Z; Lee, Kendall H; Goerss, Stephan J
Abstract: Objective . Stereotactic frame systems are the gold-standard for stereotactic surgeries, such as implantation of deep brain stimulation (DBS) devices for treatment of medically resistant neurologic and psychiatric disorders. However, frame-based systems require that the patient is awake with a stereotactic frame affixed to their head for the duration of the surgical planning and implantation of the DBS electrodes. While frameless systems are increasingly available, a reusable re-attachable frame system provides unique benefits. As such, we created a novel reusable MRI-compatible stereotactic frame system that maintains clinical accuracy through the detachment and reattachment of its stereotactic devices used for MRI-guided neuronavigation. Approach . We designed a reusable arc-centered frame system that includes MRI-compatible anchoring skull screws for detachment and re-attachment of its stereotactic devices. We validated the stability and accuracy of our system through phantom, in vivo mock-human porcine DBS-model and human cadaver testing. Main results . Phantom testing achieved a root mean square error (RMSE) of 0.94 ± 0.23 mm between the ground truth and the frame-targeted coordinates; and achieved an RMSE of 1.11 ± 0.40 mm and 1.33 ± 0.38 mm between the ground truth and the CT- and MRI-targeted coordinates, respectively. In vivo and cadaver testing achieved a combined 3D Euclidean localization error of 1.85 ± 0.36 mm ( p < 0.03) between the pre-operative MRI-guided placement and the post-operative CT-guided confirmation of the DBS electrode. Significance . Our system demonstrated consistent clinical accuracy that is comparable to conventional frame and frameless stereotactic systems. Our frame system is the first to demonstrate accurate relocation of stereotactic frame devices during in vivo MRI-guided DBS surgical procedures. As such, this reusable and re-attachable MRI-compatible system is expected to enable more complex, chronic neuromodulation experiments, and lead to a clinically available re-attachable frame that is expected to decrease patient discomfort and costs of DBS surgery.